Analysis of Heart Rate Variability in Patients Undergoing Mechanical Ventilation - Rafet Yarımoğlu; Çetin Kaymak; Namık Nebi Özcan; Sani Namık Murat; Hülya Başar; Ayşe Özcan; Alparslan Kurtul; Mustafa Sırrı Kotanoğlu (Galenos Yayinevi, 2023)
Objective:In this study, the purpose was to determine the changes in the activity of the autonomic nervous system by analyzing the parameters of heart rate variability (HRV) among patients who underwent invasive mechanical ventilation.Materials and Methods:A total of 83 patients who had been followed up in the intensive care unit for at least 24 h, without a diagnosis of any known heart disease or arrhythmia, and aged over 18 years were included in the study. Mechanically ventilated patients were included in group M (n=41) and others in group K (n=42). The electrocardiography (ECGs) of the patients was recorded for 24 h through a Holter device, which records ambulatory ECG with 3 channels.Results:There was no significant difference between the groups regarding the HRV parameters, atrial arrhythmia numbers, heart rates, RR interval times, as well as intervals of QT and QTc. It was found that the number of ventricular arrhythmias was significantly higher in the mechanically ventilated group compared to the non-mechanically ventilated group (p=0.0083).Conclusion:In conclusion, based on the results of this study, we believe that invasive mechanical ventilation did not lead to changes in the HRV parameters of the patients who were hemodynamically stable without any cardiac disease.